The terrible twos - Reed, Ishmael 1938- (St. Martin's/Marek, 1982)
"Mankind's fate rests upon St. Nicholas and a Risto-rasta dwarf named Black Peter, who together wreak mischievous havoc on WaLL Street and the Oval Office."
Keywords: Politik; Christmas -- United States -- Fiction; USA; United States -- Politics and government -- Fiction; Fiktionale Darstellung; Christmas stories; Political fiction; Satire